A basic analogue of FoxÂ´s H-function - Saxena, R. K.; Modi, G. C.; Kalla, S. L. (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
Certain basic integrals and integral representations for a basic analogue of FoxÂ´s H-function are investigated in this paper.